1982 ネン 1 ガツ エイコク ハレーキチ フキン ノ ブラント タナゴオリ ニ オケル セッピョウ チョウサ ガイホウ - 藤井, 理行; フジイ, ヨシユキ; Fujii, Yoshiyuki (1983)
P(論文) 1981年から1982年にかけての3ヵ月間, 交換科学者として英国南極観測隊(British Antarctic Survey)に参加し, 1月中旬にハレー基地のあるブラント棚氷で, 1.75m深の積雪断面観測と22mコア掘削を行った。層位解析と試料のpH測定による予察的な解析から, ハレー基地付近の積雪の堆積環境の特性として, 次のことが明らかとなった。1)積雪のpHは, 夏から秋に小さくなる傾向がある。2)コア底部の年代は1952/1953年の夏で, このため年平均涵養量は, 41.6g・cm^<-2>と推定される。3)しもざらめ層は, 秋に発達する。今後, 試料の解析(微小固体粒子濃度, 総β線量, δ^<18>O, 化学成分)と気候学的解釈を行い, この地域への大気を通しての物質輸送過程を明らかにしていく。 Glaciological work was done on the Brunt Ice Shelf near Halley Base in January 1982 by the author who participated in the British Antarctic Survey as an exchanging scientist. Preliminary results of 1.75m pit work and the analysis of a 22m long core obtained with a microdrill system indicate (1) the seasonal variation in acidity of snow, (2) the average annual balance of 41.6g・cm^<-2>・a^<-1> and (3) the depth hoar development in autumn. Further analysis of samples, such as microparticle concentration, gross β activity, δ^<18>O and chemical component, and the climatological interpretation will clarify the process of atmospheric transportation of materials to the Brunt Ice Shelf, the Antarctic coast in the Atlantic sector. departmental bulletin paper